Identifikasi Perilaku Konsumen Sebagai Upaya Peningkatan Daya Saing Usaha Ritel Skala Kecil Di Kota Semarang - Moh Khoiruddin; Anindya Ardiansari (Conference In Business, Accounting, And Management (CBAM), 2012)
Decreasing number of small-scale retail competitiveness problems (non-organized) in Semarang City which exacerbating their marginalization in the competitive retail business, is a complex issue that must be addressed. The objectives of this research is to be achieved, namely to identify consumers’ purchasing behavior in a large-scale retail (organized) and small scale (non-organized). In order to achieve the goal, after all the data were collected through interviews and questionnaires, then it is conducted with descriptive qualitative analysis and quantitative analysis (Kruskal-Walli Test). The test results conducted on consumer attitudes regarding the ten attributes that are attached to a retail store that includes the name of the store, the popularity of the store, complete facilities such as shops, security stores, convenience stores, store cleanliness, product pricing, information from media advertising, information from family / friends, as well as quality service shop in four areas of Semarang City. Meanwhile, there are only two that have a uniform response from consumers, the popularity of the store and information from media ads created by the retail stores. These results can be interpreted that the popularity of the retail store and information from media advertising on retail stores in the mind of consumers to determine their behavior in the choice of retail stores where they shop.Keywords: Consumer behavior, Competitive Advantage, Retail